The Effect of Ratio Oyster Mushroom and Tempeh with Addition of Tapioca and Pumpkin Flour on the Quality of Sausage - Elfina Simanjuntak; Herla Rusmarilin; Mimi Nurminah (Universitas Sumatera Utara, 2016)
The aim of this research was to find the effect of ratio oyster mushroom and tempeh with addition of tapioca and pumpkin flour on the quality of sausage. The research was using completely randomized design with two factors, i.e ratio oyster mushroom and tempeh (B): (0%:100%, 25%:75%, 50%:50%, 75%:25%, and 100%:0%) and ratio of tapioca and pumpkin flour (T): (100%:0%, 75%:25%, 50%:50%, 25%:75%, and 0%:100%). Parameters analyzed were moisture content, ash content, fat content, protein content, crude fiber content, organoleptic value of colour, flavor, taste, texture, and colour rendering index (oHue). The results showed that the ratio of oyster mushroom and tempeh had highly significant effect on moisture content, ash content, fat content, protein content, crude fiber content, organoleptic value of colour, flavor, taste, and texture. The ratio of tapioca and pumpkin flour had highly significant effect on protein content, organoleptic value of flavor, and texture. Interaction of the two factors had highly significant effect on organoleptic value of colour, taste, and texture. The ratio of oyster mushroom and tempeh of 75%:25% (B4) with addition of tapioca and pumpkin flour of 25%:75% (T4) produced the best sausage.